Airtight ceramic-based composite material and preparation method thereof
By preparing the interface layer on the surface of the carbon fiber prefabricated body and combining the modified resin solution and the ceramic precursor solution for multi-process combination, the problem of poor gas sealing of ceramic matrix composite materials is solved, and better gas sealing and comprehensive performance improvement is achieved.
Patent Information
- Application Number
- CN202411811857.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The existing carbon fiber reinforced ceramic matrix composites have poor gas sealing properties, resulting in gas leakage prone to high-speed and high-temperature environments.
The interface layer was prepared on the surface of the carbon fiber prefabricated body by chemical vapor deposition method, and a ceramic matrix composite material with better gas sealing was prepared by combining the modified resin solution and the ceramic precursor solution through a multi-process combination method.
It significantly improves the gas sealing properties of ceramic matrix composite materials, extends the holding time, reduces production costs, and enhances the mechanical properties, thermal stability and oxidation resistance of the materials.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic-based composite material preparation, and in particular relates to an airtight ceramic-based composite material and a preparation method thereof. Background Art
[0002] At present, conventional carbon fiber reinforced ceramic matrix composite material preparation methods include CVI+PIP, CVI+RMI (silicon melt infiltration) and other processes, which rely on the preform woven from long carbon fibers as the matrix skeleton and toughening component, and gradually fill the surrounding ceramic matrix materials, which can eventually form a dense and hard structure with a certain toughness and strong heat-resistant ceramic matrix composite material, such as the ceramic matrix composite material disclosed in Chinese patent application CN110028330A. This material that can be used in ultra-high temperature environment plays an important role in the field of aerospace. Compared with metal materials, it is light in weight and density, and can provide excellent anti-ablation and erosion performance while also ensuring the excellent mechanical properties of the material. This material has been maturely and widely used in engine accessories.
[0003] However, with the update and iteration of aviation vehicles, ceramic-based composite materials must not only adapt to the use environment of high-speed and strong scouring, but also provide better gas sealing performance, which can prevent the material from damaging the surrounding temperature-sensitive components due to heat leakage and gas leakage during operation. According to actual tests, the carbon fiber reinforced ceramic-based composite materials obtained by the current conventional method have poor gas sealing performance. Under static pressure storage conditions, the duration of the internal pressure of conventional ceramic-based composite materials dropping from 0.3MPa (gauge pressure) to 0MPa (gauge pressure) is generally less than 50 seconds, or even less than 20 seconds; the reason is that the internal structure of these ceramic-based composite materials is uneven or there are defects such as pores or microcracks. These defects form gas channels. When the material is in a closed state, a pressure difference is generated inside and outside, which will cause rapid gas leakage. Therefore, increasing the difficulty of gas circulation inside ceramic-based composite materials and extending the pressure holding time are the key to improving the gas sealing performance of ceramic-based composite materials.
[0004] In summary, it is very necessary to provide an airtight ceramic-based composite material and a preparation method thereof. Summary of the invention
[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides an airtight ceramic-based composite material and a preparation method thereof. The method of the present invention prepares a ceramic-based composite material with better gas sealing performance. The method of the present invention has a simple process, a short cycle, and low economic cost. The prepared ceramic-based composite material has broad application prospects, especially in dealing with extremely harsh use environments involved in the aerospace field, and has important pioneering positive significance.
[0006] In a first aspect, the present invention provides a method for preparing an airtight ceramic-based composite material, the method comprising the following steps:
[0007] (1) preparing an interface layer on a fiber surface of a carbon fiber preform by chemical vapor deposition to obtain a carbon fiber preform having an interface layer;
[0008] (2) preparing a modified resin solution by mixing carbide ceramic powder, furfural resin and an organic solvent, and then reacting the modified resin solution with a carbon fiber preform having an interface layer through a PIP process to obtain a modified C / C composite material;
[0009] (3) subjecting the modified C / C composite material to a melt infiltration reaction with silicon powder to obtain a melt infiltration reaction composite material;
[0010] (4) The ceramic precursor solution is reacted with the melt infiltration reaction composite material through the PIP process to produce an airtight ceramic-based composite material.
[0011] Preferably, in step (1): the interface layer is a pyrolytic carbon interface layer; and / or the density of the carbon fiber preform is 0.1 to 0.8 g / cm 3 .
[0012] Preferably, in step (2): the carbide ceramic powder is one or more of silicon carbide powder, zirconium carbide powder, and hafnium carbide powder; the particle size of the carbide ceramic powder is 1 to 1000 μm, preferably 10 to 200 μm; the organic solvent is ethanol; and / or the mass ratio of the carbide ceramic powder, furfural resin, and organic solvent is (70 to 90): (10 to 30): 1.
[0013] Preferably, in step (2): graphene is added to the modified resin solution; the mass ratio of the carbide ceramic powder, graphene, furfural resin and organic solvent is (70-90): (8-15): (10-30): 1.
[0014] Preferably, in step (3): the temperature of the infiltration reaction is 1450-1600° C., and the time is 0.25-3.5 h.
[0015] Preferably, in step (4): the ceramic precursor solution is a ceramic precursor solution containing one or more ceramic precursors of SiC, SiCN, SiBCN, SiBCNZr; preferably, the ceramic precursor solution is a polycarbosilane solution; further preferably, the polycarbosilane solution is a xylene solution of polycarbosilane, and preferably, the mass fraction of polycarbosilane in the polycarbosilane solution is 35-60%.
[0016] Preferably, in step (2) and / or step (4), the PIP process is carried out multiple times, preferably, the PIP process is carried out 2 to 4 times; each PIP process includes the processes of impregnation, curing and cracking in sequence; the impregnation is first vacuum impregnation and then pressurized impregnation, preferably, the vacuum degree of the vacuum impregnation is -0.1MPa to -0.09MPa, the time of the vacuum impregnation is 0.5 to 1h, the pressure of the pressurized impregnation is 0.5 to 2MPa, and the time of the pressurized impregnation is 0.5 to 1h; the curing temperature is 150 to 250°C, the curing time is 1 to 3h, and the curing pressure is 1 to 2MPa; the cracking temperature is 600°C to 1000°C, and the cracking time is 1 to 3h.
[0017] Preferably, Al2SiO5 powder is also added to the ceramic precursor solution in step (4).
[0018] Preferably, the particle size of the Al2SiO5 powder is 1-10 μm; and / or the mass percentage of the Al2SiO5 powder in the ceramic precursor solution is 10-20%.
[0019] In a second aspect, the present invention provides an airtight ceramic-based composite material prepared by the preparation method described in the first aspect of the present invention.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects:
[0021] (1) The present invention utilizes a multi-process combination method of "chemical vapor deposition (CVD) + impregnation curing pyrolysis (PIP) of a modified resin solution + reactive melt infiltration of silicon (RMI) + impregnation curing pyrolysis (PIP) of a ceramic precursor solution" to significantly improve the gas tightness of the ceramic-based composite material. The method of the present invention also has the advantages of short production cycle and low cost consumption. This achievement will expand the scope of use of ceramic-based composite materials or ultra-high temperature ceramic-based composite materials.
[0022] (2) The modified resin solution used in the present invention comprises carbide ceramic powder, furfural resin and organic solvent. The present invention uses the modified resin solution as an impregnation liquid to perform a PIP process on a carbon fiber preform having an interface layer, which is beneficial to improving the gas tightness of the finally prepared ceramic-based composite material. The furfural resin can act as a carrier in the impregnation stage, which helps to evenly impregnate the carbide ceramic powder into the carbon fiber preform. In the cracking stage of the PIP process, the furfural resin can also crack to produce a carbonized layer, which helps to fill the voids in the carbon fiber preform and provide support for the uniform formation of the ceramic matrix. The interface between the carbonized layer and the ceramic matrix will become denser, which helps to reduce the gas flow path. More importantly, the present invention introduces carbide ceramic powder through a PIP process using a modified resin solution as an impregnation liquid. The introduced carbide ceramic powder can effectively penetrate into the gaps and pores of the carbon fiber preform and fill the originally existing micropores and cracks, which helps to reduce the porosity inside the material, prevent the flow of gas inside the material, and improve the gas tightness. The present invention adopts the modified resin solution to carry out the PIP process, which can not only significantly improve the air tightness of the ceramic-based composite material, but also enhance the mechanical properties, thermal stability and anti-oxidation performance of the ceramic-based composite material.
[0023] (3) The present invention preferably further adds graphene to the modified resin solution. The present invention finds that the introduced graphene can form a microscopic "barrier" effect in the material. The graphene can cover the interface between the carbon fiber and the ceramic powder, fill the gaps between the ceramic powder particles, and promote the interfacial bonding between the components in the ceramic-based composite material. It can effectively reduce the microcracks or pores in the material, reduce the gas permeation path, and enhance the density of the overall structure, thereby better preventing gas permeation, which is beneficial to further improve the gas tightness of the finally prepared ceramic-based composite material.
[0024] (4) In the process of impregnation, solidification and pyrolysis (PIP) of the ceramic precursor solution, the present invention preferably adds Al2SiO5 powder (aluminum silicate powder) to the ceramic precursor solution. The present invention finds that the addition of Al2SiO5 powder can form dense phases such as aluminum silicate phase, SiO2 or Al2O3 in the ceramic matrix composite material. The formation of these phases helps to enhance the interfacial bonding force of the ceramic matrix, effectively fill the pores and cracks in the matrix, reduce the formation of pores and microcracks, and thus improve the structural density of the overall ceramic matrix, which is also beneficial to significantly improve the airtightness of the ceramic matrix composite material. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] In a first aspect, the present invention provides a method for preparing an airtight ceramic-based composite material, the method comprising the following steps:
[0027] (1) preparing an interface layer on a fiber surface of a carbon fiber preform by chemical vapor deposition to obtain a carbon fiber preform having an interface layer;
[0028] (2) preparing a modified resin solution by mixing carbide ceramic powder, furfural resin and an organic solvent, and then reacting the modified resin solution with a carbon fiber preform having an interface layer through a PIP process to obtain a modified C / C composite material; in the specific embodiments of the present invention, the furfural resins used are all liquid furfural resins; the present invention does not specifically limit the source of the furfural resin, and can use products that can be directly purchased or products synthesized by existing methods;
[0029] (3) subjecting the modified C / C composite material to a melt infiltration reaction with silicon powder to obtain a melt infiltration reaction composite material;
[0030] (4) A ceramic precursor solution is reacted with a melt infiltration reaction composite material through a PIP process to obtain an airtight ceramic-based composite material; the present invention provides a method for improving the airtightness of a carbon fiber reinforced ceramic-based composite material (e.g., an ultrahigh temperature ceramic-based composite material), and the obtained airtight ceramic-based composite material has the characteristic of high gas sealing. In the present invention, the airtight ceramic-based composite material can also be recorded as a high-airtightness ceramic-based composite material or a high-airtightness carbon fiber reinforced ceramic-based composite material.
[0031] The present invention utilizes a multi-process combination compounding method of "chemical vapor deposition (CVD) + impregnation curing pyrolysis (PIP) of modified resin solution + reactive melt infiltration silicon (RMI) + impregnation curing pyrolysis (PIP) of ceramic precursor solution" to significantly improve the gas tightness of ceramic-based composite materials. The method of the present invention also has the advantages of short production cycle and low cost consumption. This achievement will expand the scope of use of ceramic-based composite materials or ultra-high temperature ceramic-based composite materials. The present invention adopts the modified resin solution as the impregnation liquid to carry out the PIP process on the carbon fiber preform with the interface layer, which is beneficial to improve the gas tightness of the ceramic matrix composite material finally prepared, wherein the furfural resin can act as a carrier in the impregnation stage, which helps to uniformly impregnate the carbide ceramic powder into the carbon fiber preform, and in the cracking stage of the PIP process, the furfural resin can also crack to produce a carbonized layer to help fill the voids of the carbon fiber preform, and provide support for the uniform formation of the ceramic matrix. The interface between the carbonized layer and the ceramic matrix will become more compact, which helps to reduce the gas flow path, and more importantly, the present invention introduces the carbide ceramic powder through the PIP process with the modified resin solution as the impregnation liquid. The introduced carbide ceramic powder can effectively penetrate into the gaps and pores of the carbon fiber preform, and can fill the originally existing micropores and cracks, which helps to reduce the porosity inside the material, prevent the flow of gas inside the material, and improve the gas tightness. The present invention adopts the modified resin solution to carry out the PIP process, which can not only significantly improve the air tightness of the ceramic matrix composite material, but also enhance the mechanical properties, thermal stability and antioxidant properties of the ceramic matrix composite material.
[0032] Although Chinese patent application CN112457020A discloses a multifunctional ultra-high temperature ceramic-based composite material, which can also improve the air tightness of the composite material, the method is to bury one end of the porous carbon / carbon intermediate in zirconium-silicon alloy powder for infiltration reaction to obtain a porous carbon / carbon intermediate with a ZrC / SiC matrix at one end; then, the other end of the intermediate is impregnated with a hafnium-silicon integrated ceramic precursor solution, and a HfC / SiC matrix is obtained at the other end through a PIP process, and a SiC sealing layer is deposited on the surface of the ultra-high temperature ceramic matrix composed of ZrC / SiC and HfC / SiC matrices. However, this method may result in incomplete or defective interface bonding between the ZrC / SiC matrix and the HfC / SiC matrix, thereby affecting air tightness and overall sealing performance. Although the test results show that in the airtightness test, when the initial pressure is 0.5MPa, the time required for the sample pressure to drop to 0.2MPa after the gas supply is stopped can exceed 4000 seconds, showing an extremely long pressure maintenance time, but this result should be due to the fact that during the test, the multifunctional ultra-high temperature ceramic-based composite material was only tested as a gas leakage surface (conventional tests usually connect the ceramic-based composite material above the bottom-sealed metal cylinder as a gas leakage surface). Under more stringent airtightness test conditions (for example, the test conditions are that the four sides of the ceramic-based composite material cylinder are used as gas leakage surfaces and are only connected to metal materials at the upper and lower ends), the airtightness of the multifunctional ultra-high temperature ceramic-based composite material is still poor.
[0033] According to some preferred embodiments, in step (1), the interface layer is a pyrolytic carbon interface layer; and / or the density of the carbon fiber preform is 0.1 to 0.8 g / cm 3 , preferably 0.19 to 0.66 g / cm 3 The present invention does not impose any specific limitation on the process conditions for depositing the interface layer, which is a conventional technique in the art.
[0034] According to some preferred embodiments, in step (2): the carbide ceramic powder is one or more of silicon carbide powder (SiC powder), zirconium carbide powder (ZrC powder), and hafnium carbide powder (HfC powder); of course, in the present invention, the carbide ceramic includes but is not limited to silicon carbide powder, zirconium carbide powder, and hafnium carbide powder; the particle size of the carbide ceramic powder is 1 to 1000 μm, and in some specific embodiments, the particle size of the carbide ceramic powder used is 10 to 200 μm; the organic solvent is ethanol; and / or the mass ratio of the carbide ceramic powder, furfural resin, and organic solvent is (70 to 90): (10 to 30): 1.
[0035] According to some preferred embodiments, in step (2): graphene is added to the modified resin solution; the mass ratio of the carbide ceramic powder, graphene, furfural resin and organic solvent is (70-90): (8-15): (10-30): 1; the present invention preferably further adds graphene to the modified resin solution. The present invention finds that the introduced graphene can form a microscopic "barrier" effect in the material. The graphene can cover the interface between the carbon fiber and the ceramic powder, fill the gaps between the ceramic powder particles, promote the interface bonding between the components in the ceramic matrix composite material, effectively reduce the microcracks or pores of the material, reduce the gas permeation path, and enhance the density of the overall structure, thereby better preventing gas permeation, which is conducive to further improving the final prepared ceramic matrix. The gas tightness of the composite material; in addition, in the present invention, preferably, the mass ratio of the carbide ceramic powder and the graphene is (70-90): (8-15), and controlling the appropriate mass ratio can significantly improve the air tightness of the material; the present invention finds that graphene plays the best role within an appropriate dosage range, and too little or too much dosage will have an adverse effect on the overall performance of the material. If the amount of graphene is insufficient, the effect of graphene on air tightness modification will be insufficient. If the amount of graphene is too much, too much graphene may cause uneven thermal stress of the material in a high temperature environment, which may cause cracks or defects, thereby affecting the air tightness. In addition, the dispersibility of graphene is relatively poor. Too much graphene may cause the material to have an uneven structure during the preparation process, which will also affect the final performance of the composite material. In some specific embodiments of the present invention, the preparation of the modified resin solution is, for example, as follows: carbide ceramic powder and graphene are sequentially added to furfural resin, and then an organic solvent is added, followed by stirring and ultrasonic treatment; in the present invention, the stirring speed is, for example, 400 to 800 rpm, and the stirring time is, for example, 3 to 6 hours; the frequency of the ultrasonic treatment is 20 to 40 kHz, and the time of the ultrasonic treatment is, for example, 30 to 60 minutes; in the present invention, the graphene can be distributed as evenly as possible in the entire modified resin solution by stirring and ultrasonic treatment.
[0036] According to some preferred embodiments, the graphene is a graphene nanosheet, preferably, the graphene nanosheet has a sheet diameter of 5 to 10 μm and a thickness of 3 to 10 nm; in the present invention, graphene nanosheets are preferably used. The present invention finds that, compared with graphene powder, the two-dimensional structure and larger specific surface area of graphene nanosheets help to form a tight molecular network, help to form a stronger interface with other components of the ceramic-based composite material, and help to improve the gas barrier effect and prevent gas from passing through the material.
[0037] According to some preferred embodiments, in step (3): the temperature of the melt infiltration reaction is 1450-1600°C, the time is 0.25-3.5h, preferably 15-60min; step (3) of the present invention is to subject the modified C / C composite material to a molten silicon reaction treatment by an RMI process, preferably, the temperature of the melt infiltration reaction is 1450-1600°C, and the time is 0.5-3.5h. If the reaction temperature is too low or the time is too short, the silicon melt has poor fluidity, low wettability to the modified C / C composite material, and insufficient reaction; if the reaction temperature is too high or the time is too long, the carbon fiber will be damaged.
[0038] According to some preferred embodiments, in step (4): the ceramic precursor solution is a ceramic precursor solution containing one or more ceramic precursors of SiC, SiCN, SiBCN, SiBCNZr; preferably, the ceramic precursor solution is a polycarbosilane solution; further preferably, the polycarbosilane solution is a xylene solution of polycarbosilane, that is, the polycarbosilane solution consists of polycarbosilane and xylene, and preferably, the mass fraction of polycarbosilane in the polycarbosilane solution is 35-60%.
[0039] According to some preferred embodiments, in step (2) and / or step (4), the PIP process is carried out multiple times, preferably, the PIP process is carried out 2 to 4 times; each PIP process includes the processes of impregnation, curing and cracking in sequence; the impregnation is first vacuum impregnation and then pressurized impregnation, preferably, the vacuum degree of the vacuum impregnation is -0.1MPa to -0.09MPa, the time of the vacuum impregnation is 0.5 to 1h, the pressure of the pressurized impregnation is 0.5 to 2MPa, and the time of the pressurized impregnation is 0.5 to 1h; the curing temperature is 150 to 250°C, the curing time is 1 to 3h, and the curing pressure is 1 to 2MPa; the cracking temperature is 600°C to 1000°C, preferably 800 to 1000°C, and the cracking time is 1 to 3h; in the present invention, the cracking pressure is normal pressure, and the cracking is carried out in an inert atmosphere such as an argon atmosphere.
[0040] According to some specific embodiments, the preparation of the airtight ceramic-based composite material is as follows:
[0041] ① Using a CVD process to deposit amorphous carbon for a carbon fiber preform, specifically, depositing a pyrolytic carbon interface layer on the carbon fiber surface of the carbon fiber preform by chemical vapor deposition (CVD method) to obtain a carbon fiber preform having an interface layer, preferably, the initial density of the carbon fiber preform is 0.19-0.66 g / cm 3 .
[0042] ② Preparation of modified resin impregnation solution: prepare resin liquid (furfuryl ketone resin), organic solvent (ethanol), carbide ceramic powder and graphene nanosheets according to appropriate mass ratio; under stirring, gradually add carbide ceramic powder and graphene nanosheets to furfuryl ketone resin, then add organic solvent (ethanol) to obtain a mixture, and continue to stir the mixture for 3 to 6 hours, and then ultrasonically treat the mixture for 30 to 60 minutes to obtain a modified resin solution; the stirring speed is 400 to 800 rpm, and the frequency of the ultrasonic treatment is 20 to 40 kHz.
[0043] ③ Preparation of modified C / C composite material: The carbon fiber preform with an interface layer obtained in step ① is placed in the modified resin solution (impregnation solution) obtained in step ②, and after sufficient impregnation treatment (including vacuum impregnation in sequence, preferably, the vacuum degree of vacuum impregnation is -0.1MPa and pressurized impregnation, preferably, the pressurized impregnation pressure is 0.5MPa-2.0MPa), the temperature is increased for curing (preferably, the pressure is 1.0MPa-2.0MPa), and finally high-temperature pyrolysis (preferably, the high-temperature pyrolysis temperature is 800℃-1000℃); the PIP process of impregnation-curing-high-temperature pyrolysis is repeated for several rounds to obtain a modified C / C composite material mixed with carbide ceramic powder.
[0044] ④ Using the RMI process, the modified C / C composite material obtained in step ③ is subjected to a melt infiltration reaction with silicon powder to obtain a melt infiltration reaction composite material.
[0045] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, fully impregnate it (including vacuum impregnation in sequence, preferably, the vacuum degree of vacuum impregnation is -0.1MPa and pressurized impregnation, preferably, the pressurized impregnation pressure is 0.5MPa-2.0MPa), heat it for curing (preferably, the pressure is 1.0MPa-2.0MPa), and finally pyrolyze it at high temperature (preferably, the pyrolysis temperature is 800℃-1000℃); repeat the PIP process of impregnation-curing-pyrolysis for several rounds to finally obtain an airtight ceramic-based composite material.
[0046] According to some preferred embodiments, Al2SiO5 powder (aluminum silicate powder) is also added to the ceramic precursor solution in step (4); in the process of impregnation, solidification and pyrolysis (PIP) of the ceramic precursor solution, the present invention preferably adds Al2SiO5 powder (aluminum silicate powder) to the ceramic precursor solution. The present invention finds that the addition of Al2SiO5 powder can form dense phases such as aluminum silicate phase, SiO2 or Al2O3 in the ceramic-based composite material. The formation of these phases helps to enhance the interfacial bonding force of the ceramic matrix, effectively fill the pores and cracks in the matrix, reduce the formation of pores and microcracks, and thus improve the structural density of the overall ceramic matrix, which is also conducive to significantly improving the air tightness of the ceramic-based composite material; in some specific embodiments, for example, Al2SiO5 powder (aluminum silicate powder) is added to the ceramic precursor solution under stirring, and then the stirring is continued for 1 to 2 hours, and then ultrasonic treatment is performed for 30 to 60 minutes to obtain a ceramic precursor solution added with Al2SiO5 powder.
[0047] According to some preferred embodiments, the particle size of the Al2SiO5 powder is 1 to 10 μm; and / or the mass percentage of the Al2SiO5 powder in the ceramic precursor solution is 10 to 20%; the present invention finds that controlling the mass percentage of the Al2SiO5 powder in the ceramic precursor solution to 10 to 20% can ensure the formation of a sufficient number of dense phases, effectively fill pores and cracks, and enhance interfacial bonding strength, while not increasing the brittleness of the matrix too much or causing other side effects, etc. If the amount of Al2SiO5 powder added is too small, the effect of improving the air tightness of the composite material may not be obvious, and the addition of too much Al2SiO5 powder may cause the content of hard particles in the ceramic matrix to be too high. The presence of these particles may make the material more fragile, especially under high temperature or mechanical load, brittle fracture is prone to occur, and the Al2SiO5 powder content is too high, which may lead to uneven dispersion in the ceramic precursor solution, affecting the uniformity of the matrix, and in turn affecting the overall performance of the composite material.
[0048] In a second aspect, the present invention provides an airtight ceramic-based composite material prepared by the preparation method described in the first aspect of the present invention.
[0049] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and deformations according to the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples, unless otherwise specified, can all be obtained from commercial channels.
[0050] Example 1
[0051] ①The density is 0.55g / cm 3 The needle-punched carbon fiber preform flat plate is subjected to chemical vapor deposition of a pyrolytic carbon interface layer, and the deposition is carried out twice, and the time for the two pyrolytic carbon depositions is 80 hours and 50 hours respectively (a total of 130 hours), and the pyrolytic carbon interface layer is deposited until the density of the needle-punched carbon fiber preform flat plate reaches 0.80g / cm 3 , a carbon fiber preform with an interface layer is obtained.
[0052] ② Preparation of modified resin solution: prepare silicon carbide (SiC) ceramic powder, furfural resin and ethanol raw materials in a mass ratio of 87:12:1; under continuous stirring, gradually add SiC ceramic powder to furfural resin until all the SiC ceramic powder is added to furfural resin, then add ethanol to obtain a mixture, seal the final mixture, and continue to stir the mixture for 4 hours to obtain a modified resin solution; wherein the stirring speed is 600rpm.
[0053] ③Place the carbon fiber preform with the interface layer obtained in step ① into the modified resin solution (impregnation solution) obtained in step ②, after sufficient impregnation treatment, heat and cure, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to obtain a modified C / C composite material; wherein, in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 200°C, the curing time is 2h, and the curing pressure is 2MPa; the cracking temperature is 800°C, and the cracking time is 2h.
[0054] ④ Place the modified C / C composite material obtained in step ③ in silicon powder for melt infiltration reaction (melt silicon infiltration reaction) to obtain a melt infiltration reaction composite material; the melt infiltration reaction temperature is 1500° C., and the melt infiltration reaction time is 30 min.
[0055] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, after sufficient impregnation treatment, heat and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to finally obtain an airtight ceramic-based composite material; wherein the ceramic precursor solution is a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0056] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 533 seconds.
[0057] Example 2
[0058] ① The density is 0.45g / cm 3 The needle-punched carbon fiber preform flat plate is subjected to chemical vapor deposition of a pyrolytic carbon interface layer, and the deposition is carried out twice, and the time for the two pyrolytic carbon depositions is 80 hours and 50 hours respectively (a total of 130 hours), and the pyrolytic carbon interface layer is deposited until the density of the needle-punched carbon fiber preform flat plate reaches 0.73g / cm 3 , a carbon fiber preform with an interface layer is obtained.
[0059] ② Preparation of modified resin solution: prepare zirconium carbide (ZrC) ceramic powder, furfural resin and ethanol raw materials in a mass ratio of 85:14:1; under continuous stirring, gradually add ZrC ceramic powder to furfural resin until all ZrC ceramic powder is added to furfural resin, then add ethanol to obtain a mixture, seal the final mixture, and continue to stir the mixture for 4 hours to obtain a modified resin solution; wherein, the stirring speed is 600rpm.
[0060] ③Place the carbon fiber preform with the interface layer obtained in step ① into the modified resin solution (impregnation solution) obtained in step ②, after sufficient impregnation treatment, heat and cure, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to obtain a modified C / C composite material; wherein, in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 1MPa, the time of the pressurized impregnation is 1h, the curing temperature is 200°C, the curing time is 2h, and the curing pressure is 2MPa; the cracking temperature is 800°C, and the cracking time is 2h.
[0061] ④ Place the modified C / C composite material obtained in step ③ in silicon powder for melt infiltration reaction (melt silicon infiltration reaction) to obtain a melt infiltration reaction composite material; the melt infiltration reaction temperature is 1500° C., and the melt infiltration reaction time is 30 min.
[0062] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, after sufficient impregnation treatment, heat and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to finally obtain an airtight ceramic-based composite material; wherein the ceramic precursor solution is a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0063] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 595 seconds.
[0064] Example 3
[0065] ① The density is 0.45g / cm 3The needle-punched carbon fiber preform flat plate is subjected to chemical vapor deposition of a pyrolytic carbon interface layer, and the deposition is carried out twice, and the time for the two pyrolytic carbon depositions is 80h and 30h respectively (a total of 110h), and the pyrolytic carbon interface layer is deposited until the density of the needle-punched carbon fiber preform flat plate reaches 0.67g / cm 3 , a carbon fiber preform with an interface layer is obtained.
[0066] ② Preparation of modified resin solution: prepare zirconium carbide (ZrC) ceramic powder, furfural resin and ethanol raw materials in a mass ratio of 78:21:1; under continuous stirring, gradually add ZrC ceramic powder to furfural resin until all ZrC ceramic powder is added to furfural resin, then add ethanol to obtain a mixture, seal the final mixture, and continue to stir the mixture for 4 hours to obtain a modified resin solution; wherein, the stirring speed is 600rpm.
[0067] ③Place the carbon fiber preform with the interface layer obtained in step ① into the modified resin solution (impregnation solution) obtained in step ②, after sufficient impregnation treatment, heat and cure, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to obtain a modified C / C composite material; wherein, in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 200°C, the curing time is 2h, and the curing pressure is 2MPa; the cracking temperature is 800°C, and the cracking time is 2h.
[0068] ④ Place the modified C / C composite material obtained in step ③ in silicon powder for melt infiltration reaction (melt silicon infiltration reaction) to obtain a melt infiltration reaction composite material; the melt infiltration reaction temperature is 1500° C., and the melt infiltration reaction time is 30 min.
[0069] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, after sufficient impregnation treatment, heat and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to finally obtain an airtight ceramic-based composite material; wherein the ceramic precursor solution is a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0070] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 663 seconds.
[0071] Example 4
[0072] ① The density is 0.19g / cm 3 The needle-punched carbon fiber preform flat plate is subjected to chemical vapor deposition of a pyrolytic carbon interface layer, and the deposition is carried out twice, and the time for the two pyrolytic carbon depositions is 80 hours and 40 hours respectively (a total of 120 hours), and the pyrolytic carbon interface layer is deposited until the density of the needle-punched carbon fiber preform flat plate reaches 0.51g / cm 3 , a carbon fiber preform with an interface layer is obtained.
[0073] ② Preparation of modified resin solution: prepare zirconium carbide (ZrC) ceramic powder, furfural resin and ethanol raw materials in a mass ratio of 74:25:1; under continuous stirring, gradually add ZrC ceramic powder to furfural resin until all ZrC ceramic powder is added to furfural resin, then add ethanol to obtain a mixture, seal the final mixture, and continue to stir the mixture for 4 hours to obtain a modified resin solution; wherein, the stirring speed is 600rpm.
[0074] ③Place the carbon fiber preform with the interface layer obtained in step ① into the modified resin solution (impregnation solution) obtained in step ②, after sufficient impregnation treatment, heat and cure, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to obtain a modified C / C composite material; wherein, in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 200°C, the curing time is 2h, and the curing pressure is 2MPa; the cracking temperature is 800°C, and the cracking time is 2h.
[0075] ④ Place the modified C / C composite material obtained in step ③ in silicon powder for melt infiltration reaction (melt silicon infiltration reaction) to obtain a melt infiltration reaction composite material; the melt infiltration reaction temperature is 1500° C., and the melt infiltration reaction time is 30 min.
[0076] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, after sufficient impregnation treatment, heat and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to finally obtain an airtight ceramic-based composite material; wherein the ceramic precursor solution is a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0077] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 659 seconds.
[0078] Example 5
[0079] ①The density is 0.66g / cm 3The needle-punched carbon fiber preform flat plate is subjected to chemical vapor deposition of a pyrolytic carbon interface layer, and the deposition is carried out twice, and the time for the two pyrolytic carbon depositions is 80 hours and 40 hours respectively (a total of 120 hours), and the pyrolytic carbon interface layer is deposited until the density of the needle-punched carbon fiber preform flat plate reaches 0.84g / cm 3 , a carbon fiber preform with an interface layer is obtained.
[0080] ② Preparation of modified resin solution: prepare zirconium carbide (ZrC) ceramic powder, furfural resin and ethanol raw materials in a mass ratio of 78:21:1; under continuous stirring, gradually add ZrC ceramic powder to furfural resin until all ZrC ceramic powder is added to furfural resin, then add ethanol to obtain a mixture, seal the final mixture, and continue to stir the mixture for 4 hours to obtain a modified resin solution; wherein, the stirring speed is 600rpm.
[0081] ③Place the carbon fiber preform with the interface layer obtained in step ① into the modified resin solution (impregnation solution) obtained in step ②, after sufficient impregnation treatment, heat and cure, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to obtain a modified C / C composite material; wherein, in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 200°C, the curing time is 2h, and the curing pressure is 2MPa; the cracking temperature is 800°C, and the cracking time is 2h.
[0082] ④ Place the modified C / C composite material obtained in step ③ in silicon powder for melt infiltration reaction (melt silicon infiltration reaction) to obtain a melt infiltration reaction composite material; the melt infiltration reaction temperature is 1500° C., and the melt infiltration reaction time is 30 min.
[0083] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, after sufficient impregnation treatment, heat and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to finally obtain an airtight ceramic-based composite material; wherein the ceramic precursor solution is a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0084] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 513 seconds.
[0085] Example 6
[0086] ①The density is 0.60g / cm 3 The needle-punched carbon fiber preform flat plate is subjected to chemical vapor deposition of a pyrolytic carbon interface layer, and the deposition is carried out twice, and the time for the two pyrolytic carbon depositions is 80 hours and 40 hours respectively (a total of 120 hours), and the pyrolytic carbon interface layer is deposited until the density of the needle-punched carbon fiber preform flat plate reaches 0.83g / cm 3 , a carbon fiber preform with an interface layer is obtained.
[0087] ② Preparation of modified resin solution: prepare zirconium carbide (ZrC) ceramic powder, furfural resin and ethanol raw materials in a mass ratio of 78:21:1; under continuous stirring, gradually add ZrC ceramic powder to furfural resin until all ZrC ceramic powder is added to furfural resin, then add ethanol to obtain a mixture, seal the final mixture, and continue to stir the mixture for 4 hours to obtain a modified resin solution; wherein, the stirring speed is 600rpm.
[0088] ③Place the carbon fiber preform with the interface layer obtained in step ① into the modified resin solution (impregnation solution) obtained in step ②, after sufficient impregnation treatment, heat and cure, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to obtain a modified C / C composite material; wherein, in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 200°C, the curing time is 2h, and the curing pressure is 2MPa; the cracking temperature is 900°C, and the cracking time is 2h.
[0089] ④ Place the modified C / C composite material obtained in step ③ in silicon powder for melt infiltration reaction (melt silicon infiltration reaction) to obtain a melt infiltration reaction composite material; the melt infiltration reaction temperature is 1500° C., and the melt infiltration reaction time is 30 min.
[0090] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, after sufficient impregnation treatment, heat and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to finally obtain an airtight ceramic-based composite material; wherein the ceramic precursor solution is a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0091] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 603 seconds.
[0092] Example 7
[0093] ① Set the density to 0.35g / cm 3The needle-punched carbon fiber preform flat plate is subjected to chemical vapor deposition of a pyrolytic carbon interface layer, and the deposition is carried out twice, and the time for the two pyrolytic carbon depositions is 80 hours and 40 hours respectively (a total of 120 hours), and the pyrolytic carbon interface layer is deposited until the density of the needle-punched carbon fiber preform flat plate reaches 0.63g / cm 3 , a carbon fiber preform with an interface layer is obtained.
[0094] ② Preparation of modified resin solution: prepare zirconium carbide (ZrC) ceramic powder, furfural resin and ethanol raw materials in a mass ratio of 81:18:1; under continuous stirring, gradually add ZrC ceramic powder to furfural resin until all ZrC ceramic powder is added to furfural resin, then add ethanol to obtain a mixture, seal the final mixture, and continue to stir the mixture for 4 hours to obtain a modified resin solution; wherein, the stirring speed is 600rpm.
[0095] ③Place the carbon fiber preform with the interface layer obtained in step ① into the modified resin solution (impregnation solution) obtained in step ②, after sufficient impregnation treatment, heat and cure, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to obtain a modified C / C composite material; wherein, in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 200°C, the curing time is 2h, and the curing pressure is 2MPa; the cracking temperature is 900°C, and the cracking time is 2h.
[0096] ④ Place the modified C / C composite material obtained in step ③ in silicon powder for melt infiltration reaction (melt silicon infiltration reaction) to obtain a melt infiltration reaction composite material; the melt infiltration reaction temperature is 1500° C., and the melt infiltration reaction time is 30 min.
[0097] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, after sufficient impregnation treatment, heat and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to finally obtain an airtight ceramic-based composite material; wherein the ceramic precursor solution is a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0098] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 647 seconds.
[0099] Example 8
[0100] Embodiment 8 is substantially the same as Embodiment 3, except that:
[0101] ② Preparation of modified resin solution: prepare zirconium carbide (ZrC) ceramic powder, graphene nanosheets (graphene nanosheets with a sheet diameter of 5 to 10 μm and a thickness of 3 to 10 nm), furfural resin and ethanol raw materials in a mass ratio of 78:10:21:1; under continuous stirring, ZrC ceramic powder and graphene nanosheets are gradually added to the furfural resin, until the ZrC ceramic powder and graphene nanosheets are all added to the furfural resin, and then ethanol is added to obtain a mixture, and after the final mixture is sealed, the mixture is continued to be stirred for 4 hours, and then the mixture is ultrasonically treated for 45 minutes to obtain a modified resin solution; wherein the stirring speed is 600 rpm, and the frequency of the ultrasonic treatment is 40 kHz; this embodiment uses the modified resin solution obtained in step ② to carry out the same subsequent steps ③, step ④ and step ⑤ as in Example 3.
[0102] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 739 seconds.
[0103] Example 9
[0104] Example 9 is substantially the same as Example 3, except that:
[0105] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, after sufficient impregnation treatment, heat up and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-solidification-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to finally obtain an airtight ceramic-based composite material; wherein Al2SiO5 powder (aluminum silicate powder) is added to the ceramic precursor solution, and the ceramic precursor solution is composed of a polycarbosilane solution and Al2SiO5 powder, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%, and the preparation of the ceramic precursor solution is: under continuous stirring, Al2SiO5 powder (aluminum silicate powder) is added to the polycarbosilane solution, and then continuously stirred for 1.5h, Ultrasonic treatment is then carried out for 40 minutes to obtain the ceramic precursor solution, the amount of Al2SiO5 powder used is such that the mass percentage of Al2SiO5 powder in the ceramic precursor solution is 12%, wherein the stirring speed is 600r / min, and the frequency of the ultrasonic treatment is 40kHz; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0106] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 746 seconds.
[0107] Example 10
[0108] ①Same as step ① of Example 3.
[0109] ② Preparation of modified resin solution: prepare zirconium carbide (ZrC) ceramic powder, graphene nanosheets (graphene nanosheets have a sheet diameter of 5 to 10 μm and a thickness of 3 to 10 nm), furfural resin and ethanol raw materials in a mass ratio of 78:10:21:1; under continuous stirring, gradually add ZrC ceramic powder and graphene nanosheets to the furfural resin until all the ZrC ceramic powder and graphene nanosheets are added to the furfural resin, and then add ethanol to obtain a mixture, seal the final mixture, continue to stir the mixture for 4 hours, and then ultrasonically treat the mixture for 45 minutes to obtain a modified resin solution; wherein the stirring speed is 600 rpm and the frequency of the ultrasonic treatment is 40 kHz.
[0110] ③ is the same as step ③ of Example 3.
[0111] ④ is the same as step ④ of Example 3.
[0112] ⑤ Place the melt infiltration reaction composite material obtained in step ④ into the ceramic precursor solution, after sufficient impregnation treatment, heat up and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-solidification-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to finally obtain an airtight ceramic-based composite material; wherein Al2SiO5 powder (aluminum silicate powder) is added to the ceramic precursor solution, and the ceramic precursor solution is composed of a polycarbosilane solution and Al2SiO5 powder, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%, and the preparation of the ceramic precursor solution is: under continuous stirring, Al2SiO5 powder (aluminum silicate powder) is added to the polycarbosilane solution, and then continuously stirred for 1.5h, Ultrasonic treatment is then carried out for 40 minutes to obtain the ceramic precursor solution, the amount of Al2SiO5 powder used is such that the mass percentage of Al2SiO5 powder in the ceramic precursor solution is 12%, wherein the stirring speed is 600r / min, and the frequency of the ultrasonic treatment is 40kHz; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0113] In this embodiment, the prepared airtight ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an airtightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) can reach 832 seconds.
[0114] Comparative Example 1
[0115] ①The density is 0.55g / cm 3 The needle-punched carbon fiber preform flat plate is subjected to chemical vapor deposition of a pyrolytic carbon interface layer, and the deposition is carried out twice, and the time for the two pyrolytic carbon depositions is 80 hours and 50 hours respectively (a total of 130 hours), and the pyrolytic carbon interface layer is deposited until the density of the needle-punched carbon fiber preform flat plate reaches 0.80g / cm 3 , a carbon fiber preform with an interface layer is obtained.
[0116] ②Place the carbon fiber preform with the interface layer obtained in step ① into the furfural resin (impregnation liquid), after sufficient impregnation treatment, heat up and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-curing-high-temperature cracking twice, that is, a total of 3 rounds of PIP process are carried out to obtain a modified C / C composite material; wherein, in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 200°C, the curing time is 2h, and the curing pressure is 2MPa; the cracking temperature is 800°C, and the cracking time is 2h.
[0117] ③ The modified C / C composite material obtained in step ② is placed in silicon powder for melt infiltration reaction (melt silicon infiltration reaction) to obtain a melt infiltration reaction composite material; the melt infiltration reaction temperature is 1500° C., and the melt infiltration reaction time is 30 min.
[0118] ④ Place the melt infiltration reaction composite material obtained in step ③ into the ceramic precursor solution, after sufficient impregnation treatment, heat up and solidify, and finally high-temperature cracking; repeat the PIP process of impregnation-solidification-high-temperature cracking twice, that is, perform the PIP process 3 times in total, and finally obtain a ceramic-based composite material; wherein the ceramic precursor solution is a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the cracking temperature is 1000°C, and the cracking time is 2h.
[0119] In this comparative example, the prepared ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an air tightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) is 75 seconds.
[0120] Comparative Example 2
[0121] ① The density is 0.55g / cm 3 The needle-punched carbon fiber preform flat plate is subjected to chemical vapor deposition of a pyrolytic carbon interface layer, and the deposition is carried out twice, and the time for the two pyrolytic carbon depositions is 80 hours and 50 hours respectively (a total of 130 hours), and the pyrolytic carbon interface layer is deposited until the density of the needle-punched carbon fiber preform flat plate reaches 0.80g / cm 3 , a carbon fiber preform with an interface layer is obtained.
[0122] ②Place the carbon fiber preform with an interface layer obtained in step ① into a ceramic precursor solution, fully impregnate it, heat it up and solidify it, and finally pyrolyze it at high temperature; repeat the PIP process of impregnation-curing-high temperature pyrolysis 12 times, that is, perform the PIP process 13 times in total, and finally obtain a ceramic-based composite material; wherein the ceramic precursor solution is a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 50%; in each PIP process, the impregnation is first vacuum impregnation and then pressurized impregnation, the vacuum degree of the vacuum impregnation is -0.1MPa, the time of the vacuum impregnation is 0.5h, the pressure of the pressurized impregnation is 2MPa, the time of the pressurized impregnation is 1h, the curing temperature is 220°C, the curing time is 2h, and the curing pressure is 2MPa; the pyrolysis temperature is 1000°C, and the pyrolysis time is 2h.
[0123] In this comparative example, the prepared ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an air tightness test is performed. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static pressure storage conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) is 48 seconds.
[0124] Comparative Example 3
[0125] Comparative Example 3 provides a multifunctional ultra-high temperature ceramic-based composite material with reference to Example 5 of Chinese Patent CN 112457020 A.
[0126] In this comparative example, the obtained multifunctional ultra-high temperature ceramic-based composite material is processed into a ceramic-based composite material cylinder with an inner diameter of 300 mm and a wall thickness of 10 mm. Metal materials are connected to the upper and lower ends of the ceramic-based composite material cylinder, and then an air tightness test is carried out. It is measured that when the four sides of the ceramic-based composite material cylinder are used as the gas leakage surface, under static storage pressure conditions, the duration of the internal pressure dropping from 0.3 MPa (gauge pressure) to 0 MPa (gauge pressure) is 187 seconds.
[0127] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an airtight ceramic-based composite material, characterized in that: The method comprises the following steps: (1) preparing an interface layer on a fiber surface of a carbon fiber preform by chemical vapor deposition to obtain a carbon fiber preform having an interface layer; (2) preparing a modified resin solution by mixing carbide ceramic powder, furfural resin and an organic solvent, and then reacting the modified resin solution with a carbon fiber preform having an interface layer through a PIP process to obtain a modified C / C composite material; (3) subjecting the modified C / C composite material to a melt infiltration reaction with silicon powder to obtain a melt infiltration reaction composite material; (4) The ceramic precursor solution is reacted with the melt infiltration reaction composite material through the PIP process to produce an airtight ceramic-based composite material.
2. The preparation method according to claim 1, characterized in that: In step (1): The interface layer is a pyrolytic carbon interface layer; and / or The density of the carbon fiber preform is 0.1 to 0.8 g / cm 3 .
3. The preparation method according to claim 1, characterized in that: In step (2): The carbide ceramic powder is one or more of silicon carbide powder, zirconium carbide powder and hafnium carbide powder; The particle size of the carbide ceramic powder is 1 to 1000 μm, preferably 10 to 200 μm; The organic solvent is ethanol; and / or The mass ratio of the carbide ceramic powder, furfural resin and organic solvent is (70-90):(10-30):
1.
4. The preparation method according to claim 1, characterized in that: In step (2): Graphene is added to the modified resin solution; The mass ratio of the carbide ceramic powder, graphene, furfural resin and organic solvent is (70-90):(8-15):(10-30):
1.
5. The preparation method according to claim 1, characterized in that: In step (3): The temperature of the infiltration reaction is 1450-1600° C., and the time is 0.25-3.5 hours.
6. The preparation method according to claim 1, characterized in that: In step (4): The ceramic precursor solution is a ceramic precursor solution containing one or more ceramic precursors of SiC, SiCN, SiBCN, and SiBCNZr; Preferably, the ceramic precursor solution is a polycarbosilane solution; More preferably, the polycarbosilane solution is a xylene solution of polycarbosilane. Preferably, the mass fraction of polycarbosilane in the polycarbosilane solution is 35-60%.
7. The preparation method according to claim 1, characterized in that: In step (2) and / or step (4), the PIP process is performed multiple times, preferably, the PIP process is performed 2 to 4 times; Each PIP process includes the processes of impregnation, curing and cracking in sequence; The impregnation is first vacuum impregnation and then pressure impregnation. Preferably, the vacuum degree of the vacuum impregnation is -0.1MPa to -0.09MPa, the time of the vacuum impregnation is 0.5 to 1h, the pressure of the pressure impregnation is 0.5 to 2MPa, and the time of the pressure impregnation is 0.5 to 1h; The curing temperature is 150-250° C., the curing time is 1-3 hours, and the curing pressure is 1-2 MPa; The cracking temperature is 600° C. to 1000° C., and the cracking time is 1 to 3 hours.
8. The preparation method according to any one of claims 1 to 7, characterized in that: Al2SiO5 powder is also added to the ceramic precursor solution in step (4).
9. The preparation method according to claim 8, characterized in that: The particle size of the Al2SiO5 powder is 1 to 10 μm; and / or The mass percentage of Al2SiO5 powder contained in the ceramic precursor solution is 10-20%.
10. An airtight ceramic-based composite material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Ceramic matrix composite material and preparation method thereof
CN110028330A
Multifunctional ultrahigh-temperature ceramic-based composite material and preparation method thereof
CN112457020A